Fracture in drug‐eluting stents increases focal intimal hyperplasia in the atherosclerosed rabbit iliac artery. Issue 2 (23rd September 2018) - Conway, Claire; Desany, Gerard J.; Bailey, Lynn R.; Keating, John H.; Baker, Brian L.; Edelman, Elazer R.
Abstract: Objectives: Drug‐eluting stent (DES) strut fracture (SF) is associated with higher incidence of In‐stent restenosis (ISR)—return of blockage in a diseased artery post stenting—than seen with bare metal stents (BMS). We hypothesize that concomitance of drug and SF leads to greater neointimal response. Background: Controlled release of therapeutic agents, such as sirolimus and its analogs, or paclitaxel from has reduced tissue based DES failure modes compared to BMS. ISR is dramatically reduced and yet the implications of mechanical device failure is magnified. Methods: Bilateral Xience Everolimus‐eluting stents (EES) were implanted in 20 New Zealand White rabbits on normal ( n = 7) or high fat (HF)/high cholesterol (HC) ( n = 13) diets. Implanted stents were intact or mechanically fractured. Everolimus concentration was as packaged or pre‐eluted. After 21 days, stented vessels were explanted, resin embedded, MicroCT scanned, and analyzed histomorphometrically. Results: Fractured EES were associated with significant ( P < 0.05) increases in arterial stenosis and neointimal formation and lower lumen‐to‐artery area ratios compared to intact EES. Hyperlipidemic animals receiving pre‐eluted EES revealed no significant difference between intact and fracture groups. Conclusions: SF increases intimal hyperplasia, post EES implant, and worse with more advanced disease. Pre‐eluted groups, reflective of BMS, did not show significant differences, suggesting a synergistic effect of everolimus and mechanical injury, potentially explaining the lack of SF reports for BMS. Here, we report that ISR has a higher incidence with SF in EES, the clinical implication is that patients with SF after DES implantation merit careful follow‐up.